Stability Charts for Pseudostatic Stability Analysis of 3D Homogeneous Soil Slopes Using Strength Reduction Finite Element Method. (27th June 2019) - Sun, Chaowei; Chai, Junrui; Ma, Bin; Luo, Tao; Gao, Ying; Qiu, Huanfeng
Abstract : This paper uses the modified strength reduction finite element method to propose stability charts for pseudostatic stability analysis of three-dimensional (3D) homogeneous soil slopes subjected to seismic excitation. These charts are developed in a wide range of input parameters for purely cohesive slopes and cohesive-frictional slopes, respectively. Effect of the horizontal seismic load is approximately considered using the quasistatic approach. The stability charts allow to determine the factor of safety without any iterative procedure and identify the corresponding critical slope failure mechanism. A slope example is employed to illustrate the application and reliability of these stability charts.